2022
DOI: 10.3389/fimmu.2021.836119
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Recent Advances in Potential Biomarkers for Rheumatic Diseases and in Cell-Based Therapies in the Management of Inflammatory Rheumatic Diseases

Abstract: Editorial on the Research TopicRecent Advances in Potential Biomarkers for Rheumatic Diseases and in Cell-based Therapies in the Management of Inflammatory Rheumatic Diseases Inflammatory rheumatic diseases (IRD) constitute a wide spectrum of disorders encompassing inflammatory arthropathies, such as rheumatoid arthritis (RA), axial spondyloarthritis (ax-SpA) and psoriatic arthritis (PsA). It also includes connective tissue disorders, like systemic lupus erythematosus (SLE), Sjögren's syndrome (SS) or systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, some patients develop undesirable side effects, such as infections. Thus, new therapies are still needed in RA ( 2 ). Our encouraging results obtained with SuperMApo in CIA support its use in RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some patients develop undesirable side effects, such as infections. Thus, new therapies are still needed in RA ( 2 ). Our encouraging results obtained with SuperMApo in CIA support its use in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Although these chronic inflammatory disorders result from various pathogenic mechanisms, they share this non-resolving inflammation ( 1 ). Nevertheless, these chronic diseases are not always controlled by current treatments and development of new therapeutic approaches is urgently required (as recently discussed in an editorial on inflammatory rheumatic diseases ( 2 )).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory rheumatic diseases (IRD) encompass a diverse group of autoimmune conditions characterized by chronicity and heterogeneity [ 55 ]. IRD is an umbrella term for a wide range of conditions that include disorders of connective tissue (e.g., systemic lupus erythematosus, Sjögren's syndrome, and systemic sclerosis) and inflammatory arthropathies (e.g., psoriatic arthritis, axial spondyloarthritis, rheumatoid arthritis) [ 56 ]. The pathogenesis of IRD remains unclear due to its complex and variable character.…”
Section: Aim Of the Articlementioning
confidence: 99%
“…It also contains vasculitis and connective tissue disorders, like Sjögren's syndrome (SS) and systemic lupus erythematosus (SLE). This highly heterogeneous group of disorders was characterized by persistent systemic inflammation mainly affecting the musculoskeletal system and connective tissue (8)(9)(10). Previous studies have demonstrated that IRDs were associated with an increased risk of dementia, depressive disorders, and stroke (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%